A critical role of the podocyte cytoskeleton in the pathogenesis of glomerular proteinuria and autoimmune podocytopathies. (28th June 2022) - Ye, Qing; Lan, Bing; Liu, Huihui; Persson, Pontus B.; Lai, En Yin; Mao, Jianhua
Abstract: Selective glomerular filtration relies on the membrane separating the glomerular arterioles from the Bowman space. As a major component of the glomerular filtration barrier, podocytes form foot processes by the actin cytoskeleton, which dynamically adjusts in response to environmental changes to maintain filtration barrier integrity. The slit diaphragms bridge the filtration slits between neighboring foot processes and act as signaling hubs interacting with the actin cytoskeleton. Focal adhesions relay signals to regulate actin dynamics while allowing podocyte adherence to the basement membrane. Mutations in actin regulatory and signaling proteins may disrupt the actin cytoskeleton, resulting in foot process retraction, effacement, and proteinuria. Large‐scale gene expression profiling platforms, transgenic animal models, and other in vivo gene delivery methods now enhance our understanding of the interactions among podocyte focal adhesions, slit diaphragms, and actin dynamics. In addition, our team found that at least 66% of idiopathic nephrotic syndrome (INS) children have podocyte autoantibodies, which was defined as a new disease subgroup‐, autoimmune podocytopathies. This review outlines the pathophysiological mechanisms of podocyte cytoskeleton protein interactions in proteinuria and glomerular podocytopathy.